Fertilizantes especiais na cultura do milho e efeito residual na braquiária cultivada em sucessão - Leite, Bianca Stefani Arantes (2023)
The use of correctives and fertilizers is directly related to agricultural productivity, when used in appropriate doses and technologies, it favors the main crop and even succession cultivation. Special fertilizers are a promising alternative, which contributes to the efficient supply of mineral nutrients and promotes improvements in the development of the soil/plant system. The objective of this study was to compare the agronomic efficiency of special fertilizers in different doses, initially in corn crops and residual effects in brachiaria. A 6x5 factorial scheme was used, with four replications, being; the first factor represented by six sources of fertilizers (conventional mineral, cellulose-based crumbled organomineral, filter cake-based crumbled organomineral, cellulose-based granulated organomineral, polymer-coated mineral and special nitric ammonia-based mineral). The second factor was composed of five levels of nitrogen, phosphorus and potassium fertilization (0, 40, 80, 120, 160 kg ha-¹) for corn crops, totaling 120 plots. Corn was sown and after 45 days SPAD was evaluated and after 70 days, where the plants were at the V10 stage, vegetative growth variables were evaluated. After cutting the corn without disturbing the soil, Urochloa brizantha cv was sown. Marandu. After 90 days of sowing, vegetative growth variables for this species were evaluated. At the end of the experiment, the efficiency of the fertilizers was verified. The tested interaction influenced plant height (cm) and fresh mass (g) of corn. At a dose of 160 kg ha-¹, granulated organomineral fertilizers based on cellulose and mineral polymer demonstrated superiority among the other fertilizers and doses tested. As for the succession crop, there was an influence on the number of tillers and fresh mass (g), at a dose of 160 kg ha-¹, highlighting the residual power of the polymer mineral fertilizer that had the highest weight. Regarding the equivalence of fertilizers, the cellulose based mashed organomineral fertilizer demonstrated significant superiority in relation to conventional fertilizer, presenting an increase of 63.22% for corn and 60.41% for brachiaria. These results highlight the greater effectiveness of this fertilizer compared to the other sources tested.